Gratitude Correlates With Emotional Intelligence Among Industrial Employees: Rasa Syukur Berkorelasi dengan Kecerdasan Emosional di Kalangan Karyawan Industri - Surya Satria; Eko Hardi Ansyah (Academia Open, 2025)
General Background: Human resource management emphasizes employee psychological characteristics as essential components supporting workplace behavior, well-being, and organizational functioning. Emotional intelligence and positive psychological traits are frequently examined to understand employees’ emotional regulation and interpersonal functioning in organizational settings. Specific Background: Gratitude is described as an individual disposition reflecting recognition of positive experiences and divine blessings, while emotional intelligence involves self-awareness, emotional regulation, motivation, empathy, and relationship management among employees. Knowledge Gap: Empirical evidence examining the relationship between gratitude and emotional intelligence among contract employees in Indonesian industrial contexts remains limited, particularly using validated psychometric instruments. Aims: This study aimed to determine the relationship between gratitude and emotional intelligence among employees of PT. Menara Multi Mas. Results: Using a quantitative correlational design, data were collected from 117 contract employees through questionnaire administration. The gratitude scale demonstrated reliability (α = 0.738), while the emotional intelligence scale showed higher reliability (α = 0.873). Normality testing indicated normally distributed data, and Pearson correlation analysis revealed a significant positive relationship between gratitude and emotional intelligence (r = 0.698–0.699; p = 0.000). Novelty: The study provides empirical correlation evidence using adapted gratitude and emotional intelligence measurement scales within an industrial employee population. Implications: The findings indicate that higher gratitude tendencies are associated with higher emotional intelligence, suggesting the relevance of psychological development programs supporting emotional awareness and positive attitudes among employees in organizational environments. Highlights: Statistical Analysis Confirms a Significant Positive Association Between Measured Psychological Variables Among Participants. Measurement Instruments Demonstrated Acceptable Internal Consistency Based on Reliability Testing Results. Most Respondents Were Categorized Within High and Very High Levels Across Assessed Psychological Dimensions. Keywords: Gratitude, Emotional Intelligence, Employee Psychology, Organizational Behavior, Workplace Well-Being